Production, morphology and chemical-bromatological characteristics of Urochloa brizantha cv. Marandu under doses of compost from dairy cows (Research, Society and Development, 2020)
Confinement of dairy cows in Brazil is significant, with the compost badded pack barn being the most used model, generating a large amount of good quality organic compost that can be used as a fertilizer in the pastures of the farms, reducing the use of industrialized fertilizers and mitigating the environmental impacts of dairy activity. An experiment was carried out in pots under greenhouse conditions to evaluate the effect of compost doses on the production, morphology and chemical-bromatological characteristics of Urochloa brizantha cv. Marandu A completely randomized design with 3 replications and 6 treatments consisting of 6 doses of the compost: 0; 50; 10; 20; 40 and 80 g.vaso-1. Increasing compost doses resulted in higher dry matter yield, higher tillers density and higher potassium and phosphorus contents in the forage. Dairy cow compost can be used for pasture fertilization, partially replacing industrialized fertilizers.